Preparation and characterization of high temperature Sr(Ce0.6Zr0.4)0.9Y0.1O3-δ/YBaCo2O5+δ mixed proton-electron composite membrane. (12th November 2019) - Hung, I-Ming; Fu, Kuan-Chi; Khan, Azam; Wang, Yi-Hung; Lee, Sheng-Wei; Lin, Jing-Chie; Tseng, Chung-Jen; Jang, Jason S.C.
Abstract: In this study, the various Sr(Ce0.6 Zr0.4 )0.9 Y0.1 O3-δ /YBaCo2 O5+δ (SCZY/YBCO) composite ceramic membranes were prepared by sintering at different temperatures and used as proton membranes for hydrogen permeation. SCZY and YBCO powders were prepared by the citrate-ethylenediaminetetraacetic acid sol-gel process and solid-state reaction method, respectively. The chemical reaction, structure, morphology, thermal expansion, and electrical conductivity of SCZY/YBCO were investigated through X-ray powder diffraction (XRD), scanning electron microscopy (SEM), thermal mechanical analyzer (TMA) and direct current four-probe method. The relative sintered density of SCZY/YBCO membrane sintered at 1250 °C was as high as 99.5%. The conductivity of the SCZY/YBCO increased with the sintering temperature. The SCZY/YBCO sample sintered at 1250 °C exhibited the highest conductivity of 13.44 S/cm at 800 °C. The H2 permeability of the SCZY/YBCO membrane was 3.83 mL min −1 cm −2, much higher than that of SCZY at 800 °C (1.37 mL min −1 cm −2 ). Highlights: A composite high temperature proton ceramic membrane was prepared. The electrical conductivity of samples is 13.44 S/cm at 800 °C. A high hydrogen flux proton ceramic membrane was investigated. A SCZY/YBCO film on the Ni-SCZY substrate was prepared and test for hydrogen permeation.